Understanding teacher effectiveness to raise pupil attainment - Simon Burgess (IZA World of Labor, 2019)
Teacher effectiveness is the most important component of the education process within schools for pupil attainment. One estimate suggests that, in the US, replacing the least effective 8% of teachers with average teachers has a present value of 100 trillion. Researchers have a reasonable understanding of how to measure teacher effectiveness; but the next step, understanding the best ways to raise it, is where the research frontier now lies. Two areas in particular appear to hold the greatest promise: reforming hiring practices and contracts, and reforming teacher training and development.
Keywords: I26; 330; teacher effectiveness; teacher selection; teacher training